2013
DOI: 10.1016/j.actamat.2013.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular crack tip oxidation in a Ni-base superalloy

Abstract: High temperature intergranular crack tip oxidation under a single 600 s long sustained tensile load at 700 °C was studied for the Ni-base superalloy Allvac 718Plus. High-resolution analytical techniques showed oxidation to take place at and immediately ahead of the tip of an open crack, forming a closed but layered oxide structure about the prior (now oxidized) grain boundary. Near the prior grain boundary the oxide is Ni-rich with a Co-enriched layer furthest away from the metal and a Feenriched region below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 29 publications
(52 reference statements)
6
86
1
Order By: Relevance
“…3). This finding is consistent with other researches' observations using more accurate characterisation techniques, like Atom Probe Tomography (APT) and Transmission Electron Microscope (TEM) [2,11], which also showed no further damage, such as oxide, oxygen or micro cracks, far ahead of the crack tips. These results prove that the depth of oxides/oxygen damage is very limited ahead of open crack front, and obviously much smaller than the damage zone measured by d.c.p.d.…”
Section: Crack Tip Damagesupporting
confidence: 82%
See 3 more Smart Citations
“…3). This finding is consistent with other researches' observations using more accurate characterisation techniques, like Atom Probe Tomography (APT) and Transmission Electron Microscope (TEM) [2,11], which also showed no further damage, such as oxide, oxygen or micro cracks, far ahead of the crack tips. These results prove that the depth of oxides/oxygen damage is very limited ahead of open crack front, and obviously much smaller than the damage zone measured by d.c.p.d.…”
Section: Crack Tip Damagesupporting
confidence: 82%
“…In addition intergranular fracture surface morphology was observed [5,9]. However, only very limited oxide intrusions ahead of the dwell fatigue crack tip (<10 microns) are observed on 2D metallographic sections [2,11], which is contradictory to the long range diffusion argument. Although long range oxygen diffusion was suggested [5] the measurement technique adopted could not capture the uneven advance of intergranular cracks.…”
Section: Introductioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Previous studies [20,21] have shown that complex oxides of Ni, Cr, and Fe, as well as oxides formed from niobium carbides, can be formed at the crack tip in Inconel 718. This conforms with our observations where it can be seen that the crack growth rate at 550 • C increased by a factor of 100 when a dwell time of 2160 s was applied at the maximum load, see Fig.…”
Section: Discussionmentioning
confidence: 99%